2021
DOI: 10.1007/s10840-021-00944-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ablation index settings on pulmonary vein reconnection

Abstract: Purpose Ablation Index (AI) is a radiofrequency lesion quality marker. The AI value that allows effective and safe pulmonary vein isolation (PVI) is still debated.We evaluated the incidence of acute and late PV reconnection (PVR) with different AI settings and its predictors. MethodsThe Ablation Index Registry is a multicentre study that included patients with paroxysmal/persistent atrial fibrillation (AF) underwent first time ablation. Each operator performed the ablation using his preferred ablation catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…However, the author acknowledged that the success rate may have been overestimated. Then, the same team reported a higher rate of acute reconnections in AI lower group (6.8% vs. 4.6%, p = .04), and similar rates of late reconnections and complications 11 …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, the author acknowledged that the success rate may have been overestimated. Then, the same team reported a higher rate of acute reconnections in AI lower group (6.8% vs. 4.6%, p = .04), and similar rates of late reconnections and complications 11 …”
Section: Discussionmentioning
confidence: 84%
“…In the study by Solimene et al, 11 156 patients with paroxysmal and persistent AF underwent PVI with AI settings of 330–350 at posterior wall and 400–450 at anterior wall. One cardiac perfusion occurred, and 10.8% arrhythmia recurrence was observed during a follow‐up of 14 ± 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the above reasons, an optimal setting of RF energy delivered was needed to ensure the efficacy and safety of SVCI. AI as an ideal parameter for PVI showed a high single procedure success in several clinical studies ( 7 9 ). In a recent paper, Kawano et al examined the SVCI’s target AI value for the first time and revealed that 350 may be the SVCI’s target AI value, and this information could be helpful to the safety and efficacy of SVCI ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in the highpower ablation strategy (1)(2)(3)(4)(5)(6). The ablation index (AI), which weighs contact force (CF), radiofrequency time, and applied power, has been shown to aid in the creation of long-lasting ablation lesions (7)(8)(9). There are several studies, which applied AI-guided high-power ablation strategy in atrial fibrillation (AF) ablation and had been validated to improve clinical outcomes after ablation (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%